The boyfriend - Stine, R. L. (New York : Scholastic, 2004)
After Joanna breaks up with her boyfriend, Dex, he dies, but he is not through with her yet-- he is coming back for one last date.
Keywords: Man-woman relationships -- Juvenile fiction; Dating (Social customs) -- Fiction; Ghosts -- Fiction; Horror stories; Horror fiction